The potential value of blood monitoring of biologic drugs used in the treatment of rheumatoid arthritis. (February 2020) - Perry, Martin; Abdullah, Azhar; Frleta, Marina; MacDonald, Jonathan; McGucken, Andrew
The advent of biological therapies has been a major therapeutic advance in rheumatology. Many patients now enjoy improved quality of life through better disease control. The number of therapies continues to grow both within drug class (including biosimilar drugs) and via new mechanisms. For the first time, nonbiological drugs such as small-molecule inhibitors (Janus kinase inhibitors) have shown clinical equivalence. However, clinical unmet need remains with up to a third of patients commenced on a biologic therapy having minimal or no response: (a) Generally, the first biologic used secures the best response, with likelihood of remission falling thereafter with successive therapies; (b) the success of strategy trials using biological therapies can be difficult to replicate in clinical practice due to a combination of patient factors and service limitations. Accordingly, ensuring optimization of initial treatment is an important consideration before switching to alternatives. Therapeutic drug monitoring (TDM) is the measurement of serum levels of a biologic drug with the aim of improving patient care. It is usually combined with detection of any antidrug antibodies that could neutralize the effect of the therapy. This technology has the potential to be a form of 'personalized medicine' by individualizing therapy, in particular, dosing and likelihood of sustained treatment response. It requires a clear relationship between drug dose, blood concentration and therapeutic effect. This paper will outline the technology behind TDM and unpack what we can learn from our colleagues in gastroenterology, where the adoption of TDM is at a more advanced stage than in rheumatology. It will explore and set out a number of clinical scenarios where rheumatologists might find TDM helpful in day-to-day practice. Finally, an outline is given of international developments, including regulatory body appraisals and guideline development.